Efficacy of buffered sodium citrate alone and in combination with sodium diacetate against Listeria monocytogenes on beef franks - E. Ceylan; M. Hajmeer; James L. Marsden (Kansas Agricultural Experiment Station Research Reports, 2003)
We assessed the antimicrobial efficacy of buffered sodium citrate alone and in combination with sodium diacetate against L. monoyctogenes on beef frank samples stored at 39°F. Initial inoculum level of L. monocytogenes was 1.5 log colony forming units (CFU)/cm2. After 6 weeks of incubation at 39°F, the pathogen reached 5.4 log CFU/cm2 in the control sample, but was 1.2 log CFU/cm2 and 0.85 log CFU/cm2 in samples treated with 1% buffered sodium citrate alone and in combination with 0.1% sodium diacetate, respectively. Use of buffered sodium citrate and the combination of buffered sodium citrate and sodium diacetate should improve safety of ready to eat foods by controlling L. monocytogenes during storage.
Keywords: Cattlemen' s Day; 2003; Kansas Agricultural Experiment Station contribution; no. 03-272-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 908; Beef; Sodium citrate; Sodium diacetate; Listeria monocytogenes; Beef franks